Quantum leap Season 4 Disc 2 - Bernheim, Robin; Wade, Harker; Ruppenthal, Chris; Bellisario, Donald P.; Addison, Anita W.; Bakula, Scott; Stockwell, Dean, 1936-2021.; Bunch, Velton Ray.; Edmonson, Greg.; Post, Mike.; Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2006)
Season four delivers even more exciting leaps with 22 unforgettable episodes following Dr. Sam Beckett's extraordinary time-travel adventures.
A single drop of rain -- Unchained -- The play's the thing -- Running for honor -- Temptation eyes -- The last gunfighter -- A song for the soul -- Ghost ship.
Title from container.
Originally broadcast as a episode 9-16 of the television series in 1991-1992.
Editors, Mario Di Gregorio [and others] ; music, Velton Ray Bunch, Greg Edmonson, Mike Post.
Scott Bakula, Dean Stockwell.
Not rated.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital 2.0, double sided.
Keywords: Time travel; Drama; Science fiction television programs; Television programs